CR- Submanifolds of a Nearly Trans-Hyperbolic Sasakian Manifold with a Quarter Symmetric Semi Metric Connection - Rahman, Shamsur (Jurnal Matematika; Vol 6 No 2 (2016), 2022)
The object of the present paper is to initiate the study contact CR- submanifolds of a nearly trans-hyperbolic Sasakian manifold with a quarter symmetric semi metric connection. For this, some properties of CR- submanifolds of a nearly trans-hyperbolic Sasakian manifold with a quarter symmetric semi metric connection are investigated which conclude that CR- submanifolds of a nearly trans-hyperbolic Sasakian manifold with a quarter symmetric semi metric connection exists with respect to the ?????horizontal and ?????vertical.
Keywords: CR-submanifolds; nearly trans-hyperbolic Sasakian manifold; quarter symmetric semi metric connection; Gauss and Weingarten equations parallel distributions